Stabilization of Ni-containing Keggin-type polyoxometalates with variable oxidation states as novel catalysts for electrochemical water oxidation † - Li, X; Ng, BKY; Ho, P; Jia, C; Shang, J; Yoskamtorn, T; Pan, X; Li, Y; Li, G; Wu, T; Soo, Y; He, H; et al. (Royal Society of Chemistry, 2024)
The development of new recyclable and inexpensive electrochemically active species for water oxidation catalysis is the most crucial step for future utilization of renewables. Particularly, transition metal complexes containing internal multiple, cooperative metal centers to couple with redox catalysts in the inorganic Keggin-type polyoxometalate (POM) framework at high potential or under extreme pH conditions would be promising candidates. However, most reported Ni-containing POMs have been highly unstable towards hydrolytic decomposition, which precludes them from application as water oxidation catalysts (WOCs). Here, we have prepared new tri-Ni-containing POMs with variable oxidation states by charge tailored synthetic strategies for the first time and developed them as recyclable POMs for water oxidation catalysts. In addition, by implanting corresponding POM anions into the positively charged MIL-101(Cr) metal–organic framework (MOF), the entrapped Ni2+/Ni3+ species can show complete recyclability for water oxidation catalysis without encountering uncontrolled hydrolysis of the POM framework. As a result, a low onset potential of approximately 1.46 V vs. NHE for water oxidation with stable WOC performance is recorded. Based on this study, rational design and stabilization of other POM-electrocatalysts containing different multiple transition metal centres could be made possible.